2020
DOI: 10.1111/odi.13312
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal timing for implant placement in oral cancer patients? A scoping literature review

Abstract: Background: Oral cancer patients can benefit from dental implant placement. Traditionally, implants are placed after completing oncologic treatment (secondary implant placement). Implant placement during ablative surgery (primary placement) in oral cancer patients seems beneficial in terms of early start of oral rehabilitation and limiting additional surgical interventions. Guidelines on the ideal timing of implant placement in oral cancer patients are missing. Objective: To perform a scoping literature review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…For example, a recent retrospective, case‐control study concluded that placing immediate dental implants at the time of surgery does not increase radiotherapy treatment toxicities 20 . Another recent scoping review concluded that the combination of surgery and placement of dental implant should be considered as standard care for HNC survivors 21 . Other dental clinicians recommend replacement of missing teeth with dentures as this is less expensive, noninvasive, takes less time, and can be delivered safely without involvement of a specialist 22 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent retrospective, case‐control study concluded that placing immediate dental implants at the time of surgery does not increase radiotherapy treatment toxicities 20 . Another recent scoping review concluded that the combination of surgery and placement of dental implant should be considered as standard care for HNC survivors 21 . Other dental clinicians recommend replacement of missing teeth with dentures as this is less expensive, noninvasive, takes less time, and can be delivered safely without involvement of a specialist 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Advanced tumours can result in large defects, requiring surgical reconstruction (Vaughan, Bainton, & Martin, 1992) As implant placement during primary reconstruction shortens the interval between surgery and dental rehabilitation, the number of orally rehabilitated patients will increase (Alberga et al, 2020;Urken et al, 1989).…”
Section: Rehab Ilitation Of Mandibul Ar Defec Tsmentioning
confidence: 99%
“…This allows for the preferred prosthodontic rehabilitation of head and neck patients. For example, choices in planning, positioning and amount of endosseous oral implants or oncology zygomatic implants are key factors for retention of the prosthetic construction (Alberga et al, 2020; Hackett, El‐Wazani, & Butterworth, 2020). Literature emphasizes the importance of an immediate implant procedure as it has been shown that placement of mandibular implants in edentulous patients during ablative surgery results in a higher number of patients with functioning mandibular dentures after completion of oncologic therapy (Korfage et al., 2011; Mizbah et al., 2013; Wetzels et al, 2017).…”
Section: Pretreatment Screeningmentioning
confidence: 99%
“…Following RT, dental extractions from the bone which has received high dose radiation should only be undertaken if unavoidable-endodontic treatment and decoronation should be considered first [302]. In the context of oral health and dental rehabilitation, treating periodontal disease and restoring occlusal function are important for mastication of food and bolus preparation, facilitating nutritional intake, and reducing the risk of aspiration of food and/or of oral micro-organisms into the respiratory tract [303][304][305][306].…”
Section: Oral Health In Head and Neck Cancermentioning
confidence: 99%